PARADIGMA DAN STRATEGI DAKWAH HUMANIS PADA KOMUNITAS MINORITAS (Studi Kasus Kaum Waria di Kota Kudus) - Rosyid, Moh (Analisis: Jurnal Studi Keislaman, 2012)
The existence  of a community,  wherever  it my be, if it were looked as  dissimilar  as  their  environment,  especially  those  of  minorities, has always had a minor response from the communities  of majority. This is exactly experienced by the transgender community. Those of transvestites are being viewed negatively due to  the irregularities in the way they live and behave. This article tries to formulate a model of humanistic  proseltizing  that is not against  the existence  of such transgender community as objects of the proselytizing (mad’u). Based on a research  on the portrait  of transvestites  in the city of Kudus, Central Java, the author suggests that if the  notion to proportionally placed transvestites is overlooked or that the transgender community is out of consideration for being targeted community (mad’u), then we basically have missed the humanistic character of the mission itself. The  existence  of  transgender  in a religious  observance  is,  indeed, indifference as those of non-transgender community that needs touches of religious  values by a preacher. Denial of human existence to those of transgender (the humanist character) is fundamentally at odds with the mandate of Law Number 39 Year 1999 on Human Rights. If  this is the case, then, it needs to takes  that of humanistic proselytizing approach which  humanize all human beings, including those of transvestites.